Use of Mean Platelet Volume and Neutrophil-To-Lymphocyte Ratio as Predictors of Postoperative Transfusion Needs and Morbidity in Total Knee and Hip Arthroplasties - Davulcu, Cumhur Deniz; Davutluoğlu, Ece (Cerrahpaşa Medical Journal, 2024)
Objective: This study aimed to evaluate the diagnostic value of the neutrophil-to-lymphocyte ratio (NLR) as a predictor of postoperative blood transfusion requirements, intensive care unit (ICU) admission, and prolonged hospital stay in patients undergoing total knee arthroplasty (TKA) and total hip arthroplasty (THA). Methods: A total of 229 patients who underwent TKA and 201 patients who underwent THA between January 2016 and December 2023 were retrospectively analyzed. The predictive utility of NLR, mean platelet volume (MPV), platelet count, and other hematological markers was assessed. Inclusion criteria focused on patients aged 45-80, while those with significant comorbidities, such as cancer or hematological disorders, were excluded. The primary outcomes measured were postoperative blood transfusion need, ICU admission, and hospital stay duration. Results: The neutrophil-to-lymphocyte ratio demonstrated a statistically significant association with the need for postoperative blood transfusion in both TKA and THA patients (P < .05). However, other markers, including the MPV/platelet count ratio, did not show a significant correlation with postoperative ICU admission or prolonged hospital stays. No significant predictive value was identified for other hematological parameters. Conclusion: Neutrophil-to-lymphocyte ratio may be a useful, cost-effective marker for predicting the need for blood transfusion in arthroplasty patients. However, the MPV/platelet count ratio did not show predictive value in this context. Further large-scale, prospective studies are necessary to confirm the utility of NLR and explore other potential predictive markers for postoperative outcomes in TKA and THA patients. Cite this article as: Davulcu CD, Davutluoğlu E. Use of mean platelet volume and neutrophil-to-lymphocyte ratio as predictors of postoperative transfusion needs and morbidity in total knee and hip arthroplasties. Cerrahpaşa Med J. 2024;48(3):275-278.